The Effect of Metacognitive Strategy on The English Learners’ Vocabulary Mastery - Damanik, Bernieke Anggita Ristia (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
This study was aimed at investigating the effect of metacognitive strategy on the English Learners’ Vocabulary Mastery at FKIP Nommensen Pematangsiantar. This research was conducted by applying quantitative research design. The data were taken from English Learners in the classroom. This research is conducted by applying experimental research design. In this research, there are two procedures which is made to collect the data, there are treatment and test. For the first step the writer gave the treatment for each group. Experimental group got three times treatment by using metacognitive strategy and control group got 3 times treatment also by using conventional method. The test. is a test conducted after conducting the treatment. After explaining the material and giving the exercise both of the groups are given the same test to know the result of the treatment. The scores will be analyzed to see the differences of the group.